The Changing Narrative of Stereotypical Portrayals of Women in Advertising - Mabye, Kgaugelo (The IIE, 2022)
Unspoken social taboos are seriously affecting society (Kuegler, 2020), and embracing this conversation is a necessary first step toward achieving a more equitable society (Green, 2020). Brands have a platform to speak out about social taboos in order to influence social dialogue, because failure to do so perpetuates false and harmful narratives about women (Mihalčová, Pružinský, & Gontkovičová, 2015). As a result, the researcher looked into the Always brand, which used social taboos to address stereotypes in their 'Like a Girl' advertisement, to see if indeed social dialogue was achieved. To accomplish this, a qualitative in-depth interview with the Head of Brand at Always was conducted, along with a quantitative survey, in order to gain a broad and deep understanding of the phenomenon. The study's findings revealed that consumers value the need for social taboos to be discussed, and they look to brands to take a similar stance and to serve as their mouthpiece. As a result, brands must take this stance authentically, rather than as a gimmick to attract consumers' attention, otherwise, it has the potential to trivialise a serious social crisis.
How brands Can Use Social Taboos to Influence Social Dialogue
Keywords: Gender; Stereotypes; Disinformation; Consumer behaviour